Examination of the Structure and Grade-Related Differentiation of Multidimensional Self-Concept Instruments for Children Using ESEM. Issue 2 (2nd April 2016) - Arens, A. Katrin; Morin, Alexandre J. S.
Abstract : This study is a substantive-methodological synergy in which exploratory structural equation modeling is applied to investigate the factor structure of multidimensional self-concept instruments. On the basis of a sample of German students ( N = 1958) who completed the Self-Description Questionnaire I and the Self-Perception Profile for Children, the results supported the superiority of exploratory structural equation modeling compared with confirmatory factor analyses for both instruments. Exploratory structural equation modeling resulted in lower factor correlations and substantively meaningful cross-loadings. The authors also proposed and contrasted 3 mechanisms for testing grade-related differences in the differentiation of self-concept facets and found no evidence of increased differentiation between Grades 3 to 6.